Spatial differences in diet quality and economic vulnerability to food insecurity in Bangladesh: Results from the 2016 household income and expenditure survey - Mitu, Mst. Maxim Parvin; Islam, Khaleda; Sarwar, Sneha; Ali, Masum; Amin, Md. Ruhul (MDPI, 2022)
The study explored the spatial differences in diet quality and economic vulnerability to food insecurity with the association of sociodemographic characteristics at the household level in Bangladesh. This study was a secondary data analysis of Household Income and Expenditure Survey (HIES) data of 2016. Both statistical and spatial analyses were applied while assessing diet qualities in terms of the household dietary diversity score (HDDS), percentage of food energy from staples (PFES), and percentage of expenditure on food (PEF) as an indicator of the economic vulnerability to food insecurity (EVFI). The study’s findings revealed that the quality of people’s diets worsened as they moved from urban to rural area, and EVFI increased as they moved from the center to the periphery of the country. Nationally, the average HDDS was about 6.3, and the average PFES per household per day was about 70.4%. The spatial distribution of HDDS and PFES showed that rural regions in terms of settlements and the north, northwest and southeast regions had mostly low diet diversity. Besides, the average PEF per household per day was about 54%, with the highest in Mymensingh (57.4%) and the lowest in Dhaka division (50.2%). The average PEF in the households illustrated was highest in rural (55.2%) and lowest in the city (45.7%). Overall, based on the PEF at the sub-district level, the medium level of vulnerability comprised the highest share (69%) in Bangladesh. Age, gender, literacy, educational qualification and religion of the household’s head along with the number of earners, monthly income, area of settlements and divisions were significantly correlated with HDDS, PFES and EVFI. The study findings suggest that targeted interventions, including access to education, women empowerment and employment generation programs should be implemented in peripheral areas (north, northwest and southeast) to increase diet quality and minimize economic vulnerability to achieve sustainable food and nutrition security in Bangladesh.